PERANCANAGAN VISUAL IDENTITY MAHA PUDING BUKITTINGGI - REZI ASMARNI, Dra. Zubaidah, M.Sn., Eliya Pebriyeni, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
Maha Pudding is one of the businesses that provides dessert in the form of ice cream pudding located at Jalan Pemda, Pasar Bawah, Bukittinggi. Maha Puding was founded in March 2006 and managed by Anjar Rahman as the owner and founder of Maha Puding until now. Maha Puding requires a visual identity that includes logos, colors, and fonts, and rules in its application, according to the reference set by the designer in the manual book as the main media, in order to establish a consistent identity, enhance the business image, and become a distinctive and unique feature for Maha Puding.The design method that I use is the glasbox method while in the data analysis the author uses SWOT analysis, strength (weakness), weakness (Weakness), chance (Oppurtunity), and threat (Threat) from Maha Puding. The main media used in the design of the Maha Puding logo is the media manual book. Then the application media include business cards, envelopes, letterhead, sales invoices, stamps, table numbers, menu lists, aprons, t-shirts, posters and x-banners.Keywords: Visual Identity, Maha Puding, Logo